Preparing to caress: a neural signature of social bonding - Campagnoli, Rafaela R.; Krutman, Laura; Vargas, Claudia D.; Lobo, Isabela; Oliveira, Jose M.; Oliveira, Leticia; Pereira, Mirtes G.; David, Isabel A.; Volchan, Eliane (Frontiers in Psychology, 2015)
It is assumed that social bonds in humans have consequences for virtually all aspects of behavior. Social touch-based contact, particularly hand caressing, plays an important role in social bonding. Pre-programmed neural circuits likely support actions (or predispositions to act) towards caressing contacts. We searched for pre-set motor substrates towards caressing by exposing volunteers to bonding cues and having them gently stroke a very soft cloth, a caress-like movement. The bonding cues were pictures with interacting dyads and the control pictures presented non-interacting dyads. We focused on the readiness potential, an electroencephalographic marker of motor preparation that precedes movement execution. The amplitude of the readiness potential preceding the grasping of pleasant emotional-laden stimuli was previously shown to be reduced compared with neutral ones. Fingers flexor electromyography measured action output. The rationale here is that stroking the soft cloth when previously exposed to bonding cues, a compatible context, would result in smaller amplitudes of readiness potentials, as compared to the context with no such cues. Exposure to the bonding pictures increased subjective feelings of sociability and decreased feelings of isolation. Participants who more frequently engage in mutual caress/groom a “significant other” in daily life initiated the motor preparation earlier, reinforcing the caress-like nature of the task. As hypothesized, readiness potentials preceding the caressing of the soft cloth were significantly reduced under exposure to bonding as compared to control pictures. Furthermore, an increased fingers flexor electromyographic activity was identified under exposure to the former as compared to the latter pictures. The facilitatory effects are likely due to the recruitment of pre-set cortical motor repertoires related to caress-like movements, emphasizing the distinctiveness of neural signatures for caress-like movements.